Edukasi Masyarakat: Akuntabilitas Islam dalam Merespons Krisis Palestina - Marlina, Lilis; Luthfi, Luthfi (Universitas Negeri Gorontalo, 2025)
This community service program aimed to educate community leaders in Subulussalam City about Islamic accountability in responding to the Palestinian crisis. The topic is crucial due to the low level of ideological literacy and the dominance of emotional narratives on social media, which influence public understanding. The activity was conducted in one day using a participatory method consisting of a 60-minute lecture and a 90-minute discussion, involving 31 participants from various religious and community backgrounds. The lecture applied the dakwah bil hikmah approach, while the discussion followed the maieutic method. Results showed that 93.5% of participants recognized concern for Palestine as part of Islamic accountability and a religious obligation. Additionally, 77.4% were willing to call Muslims back to a comprehensive practice of Islam (kaffah), and 71% were prepared to organize study circles to support dakwah promoting Islam as rahmatan lil ‘alamin. These findings affirm that a short educational intervention can effectively foster ideological awareness and real community-level dakwah commitment.